Силовая электроника в смарт сетях - Жуйков, В.Я. (Технічна електродинаміка, 2012)
Discusses features of the criteria for evaluating the quality of electricity, and also integrated indicators on the basic and higher harmonics. Shown that power converters work with pulse-phase regulation of alternating voltage induces a change of reactive power component of the power network. Review the functions of power electronics devices in Smart Grids.